Desain Sistem Tata Kelola Dana Desa Berbasis Cloud Server - Algifanri Maulana; Cosmas Eko Suharyanto (LPPM Universitas Putera Batam, 2018)
This study aims to create a display of innovation systems in managing village funds by preparing vcloud computing-based innovations to manage all data generated so that local governments can help oversee the absorption of village budget funds in realtime and transparency. In this study researchers used qualitative methods because in this study focused on researching objects directly. This research is done by researching directly on innovation system of Batam City area. The research method by interview and observation from secondary data taken from the realization of village fund budget that has been running so as to produce data that can be controlled through cloud server based application. Stages performed in this design using desktop-based Visual studio applications which will be controlled via Client & Server as a controller for processing and processing data. And for the database using postgresSQL database where later technology applications are made will be integrated via the Internet network. The results of this study is to provide a description of desktop system design as a reference to manage the village funds are transparent with the help of cloud server technology so that the data processed and processed can be monitored using the internet. It can also help the urban government to innovate village-based village fund governance governance so that funds that have been prepared and distributed can be controlled quickly, effectively and targeted through technology applications.